The role of WNT10B in normal prostate gland development and prostate cancer. Issue 14 (21st August 2019) - Madueke, Ikenna; Hu, Wen‐Yang; Hu, Danping; Swanson, Steven M.; Vander Griend, Donald; Abern, Michael; Prins, Gail S.
Abstract: Background: WNT signaling is implicated in embryonic development, and in adult tissue homeostasis, while its deregulation is evident in disease. This study investigates the unique roles of canonical WNT10B in both normal prostate development and prostate cancer (PCa) progression. Methods: Organ culture and rat ventral prostates (VPs) were used to study Wnt10b ontogeny and growth effect of WNT10B protein. PB‐SV40 LTag rat VPs were utilized for Wnt expression polymerase chain reaction (PCR) array and immunohistochemistry. Human localized PCa tissue microarrays (TMAs) were investigated for differential WNT10B expression. Human RNA‐seq data sets were queried for differential expression of WNT10B in metastatic and localized PCa. Knockdown of WNT10B in PC3 cells was utilized to study its effects on proliferation, stemness, epithelial to mesenchymal transition (EMT), and xenograft propagation. Results: Wnt10b expression was highest at birth and rapidly declined in the postnatal rat VP. Exogenous WNT10B addition to culture developing VPs decreased growth suggesting an antiproliferative role. VPs from PB‐SV40 LTag rats with localized PCa showed a 25‐fold reduction in Wnt10b messenger RNA (mRNA) expession, confirmed at the protein level. Human PCa TMAs revealed elevated WNT10B protein in prostate intraepithelial neoplasia compared with normal prostates but reduced levels in localized PCa specimens. In contrast, RNA‐seq data set of annotated human PCa metastasis found a significant increase in WNT10B mRNA expression compared with localized tumors suggesting stage‐specific functions of WNT10B. Similarly, WNT10B mRNA levels were increased in metastatic cell lines PC3, PC3M, as well as in HuSLC, a PCa stem‐like cell line, as compared with disease‐free primary prostate epithelial cells. WNT10B knockdown in PC3 cells reduced expression of EMT genes, MMP9 and stemness genes NANOG and SOX2 and markedly reduced the stem cell‐like side population. Furthermore, loss of WNT10B abrogated the ability of PC3 cells to propagate tumors via serial transplantation. Conclusions: Taken together, these results suggest a dual role for WNT10B in normal development and in PCa progression with opposing functions depending on disease stage. We propose that decreased WNT10B levels in localized cancer allow for a hyperproliferative state, whereas increased levels in advanced disease confer a stemness and malignant propensity which is mitigated by knocking down WNT10B levels. This raises the potential for WNT10B as a novel target for therapeutic intervention in metastatic PCa.